Managers guide to understanding effective contract evaluation - Adoranti, Frank (Kent : Global Professional Publishing, 2009)
This book gives managers and employees an understanding of how organisations review and evaluate contracts in the course of business and how to deal with typical problem clauses.
Includes index.
rua 09/12/13
Loans
Keywords: Contracts; Contracts evaluation; Contracts management